Screening of Deshampsia Antarctica and Colobanthus Quitensis Plants for Viral Agents - S. V. Dolgorukova; I. G. Budzanivska; F.P. Demjanenko; V. P. Polishchuk (Ukrainian Antarctic Journal, 2010)
Priority research in virology is the study of Antarctic plant viruses, so we can talk about high diversity of antigenic determinants among these plants. Therefore the purpose of this work is the study of plant viruses and the screening of viral antigens in plants Deschampcia antarctica and Colobanthus quitensis. Samples were selected on many islands, including islands of Galindez, Barkhan, Yalour, Pitterman, Uruguay, Skua, Lipman, Barselot, Dorboks, Vinger, and capes Rassmusen and Tuksen. The samples were tested for viruses of plants that have a narrow range of hostplants Brome mosaic virus (BrMV), Barley stripe mosaic hordeivirus (BSMV) and Cucurbit aphidborne yellows virus (CABYV) and wide range of host-plants Cucumber mosaic virus (CMV), Tomato spotted wilt virus (TSWV), Alfalfa mosaic virus (AMV), Wheat streak mosaic virus (WSMV), Barley yellow dwarf virus (BaYDV), Zucchini yellow mosaic virus (ZYMV), Tomato aspermy virus (TAV),Arabis mosaic virus (ArMV), Pepino mosaic virus (PMV), Cucumber green mottle mosaic virus (CGMMV), Tobacco mosaic virus (TMV),  Potato virus X (PVX) та Potato virus Y (PVX). Using ELISA, the presence of viral antigens belonging to different taxonomic groups, such as AMV (Alfamovirus) and CMV (Bromoviridae, Cucumovirus), CGMMV (Tobamovirus) and TSWV (Bunyaviridae, Tospovirus) was detected. Therefore, basing on the findings, we suggest that Antarctica is a large reservoir for storing of variety of organisms, including viruses. This in turn makes it a subject of study for many researchers.